Early ontogeny of immune cells and their functions in the fetal pig - Trebichavský, I; Tlaskalová, H; Cukrowska, B; Splíchal, I; Sinkora, J; Oeháková, Z; Sinkora, M; Pospísil, R; Kováøù, F; Charley, B; Binns, R; White, A (Veterinary immunology and immunopathology, 1996)
The origin of immune cells and their products have been studied in the prenatal period in miniature pigs. Macrophages were first detected on day 25, and myelocytes and lymphoid cells by day 28. Membrane antigens SLA-DR and CD45 were found by day 22, membrane molecules MG-7, 8/1, CD1, CD2 and 74-22 by day 28, Gamma/delta T cells were found initially in extrathymic sites (in the liver). The first gamma/delta T cells were detected as early as 40 days of gestation. The expression of fibronectin, Thy-1 and its message, Ig isotypes and the first induction of IFN alpha were described.
Keywords: imunitní systém; prasata; Embryonic and Fetal Development; Granulocytes; Swine; buněčná diferenciace; Immune System; granulocyty; Lymphocytes; Animals; Macrophages; embryonální a fetální vývoj; lymfocyty; zvířata; Cell Differentiation; makrofágy